Illuminating the dark space of neutral glycosphingolipidome by selective enrichment and profiling at multi-structural levels - Wang, Zidan; Zhang, Donghui; Wu, Junhan; Zhang, Wenpeng; Xia, Yu (Nature communications, 2024)
Glycosphingolipids (GSLs) are essential components of cell membranes, particularly enriched in the nervous system. Altered molecular distributions of GSLs are increasingly associated with human diseases, emphasizing the significance of lipidomic profiling. Traditional GSL analysis methods are hampered by matrix effect from phospholipids and the difficulty in distinguishing structural isomers. Herein, we introduce a highly sensitive workflow that harnesses magnetic TiO 2 nanoparticle-based selective enrichment, charge-tagging Paternò–Büchi reaction, and liquid chromatography-tandem mass spectrometry. This approach enables mapping over 300 distinct GSLs in brain tissues by defining sugar types, long chain bases, N-acyl chains, and the locations of desaturation and hydroxylation. Relative quantitation of GSLs across multiple structural levels provides evidence of dysregulated gene and protein expressions of FA2H and CerS2 in human glioma tissue. Based on the structural features of GSLs, our method accurately differentiates human glioma with/without isocitrate dehydrogenase genetic mutation, and normal brain tissue. The molecular profiling of glycosphingolipids (GSLs) is hindered by the coexistence of abundant phospholipids and diverse isomers. The authors introduce a highly sensitive workflow that maps out the structural atlas of neutral GSLs, previously deemed a “dark space” within the lipidome.